The Beneficial Effects of Sulfur-containing Amino Acids on Cisplatininduced Cardiotoxicity and Neurotoxicity in Rodents - Rosic, Gvozden; Joksimovic, Jovana; Selakovic, Dragica; Jakovljevic, Vladimir; Zivkovic, Vladimir; Srejovic, Ivan; Djuric, Marko; Djuric, Dragan (Current Medicinal Chemistry, 2018)
Background: Cisplatin is one the most frequently used chemotherapeutic drugs for several decades. Although its antineoplastic effect has been reported in treatment of numerous malignances, various adverse effects seem to be the crucial limiting factor for its administration. Objective: Beside the most commonly described nephro- and hepatotoxicity, cisplatin therapy is also accompanied with gastrointestinal, reproductive, hematological, cardiovascular and neurological side effects. Since it has been reported that cisplatin induce oxidative damage in various tissues, it seems reasonable to investigate an antioxidant supplementation as potential therapeutical approach for attenuation of cisplatin toxicities. Methods: We performed a structured search of bibliographic databases for research literature using a focused review question and inclusion/exclusion criteria. The quality of retrieved papers (101 in total) was appraised using standard tools. Results: Numerous antioxidants (such as thiol compounds, polyphenols, vitamins, etc.) had been reported for their beneficial effects on cisplatin-induced cardiotoxicity. The effects of various antioxidants, including sulfur-containing amino acids, have also been explored for mitigation of cisplatin neurotoxicity. However, the results for antioxidant supplementation in reduction of cisplatin-induced toxicities are still to be applied in clinical trials. Conclusion: Considering the facts that sulfur-containing amino acids: (a) do not interfere with chemotherapeutics antitumor action; (b) do not exhibit any toxic effect (unless applied in dose several times above the recommended); and (c) produce significant protective effects on some cisplatin-induced toxicities connected to augmentation of oxidative damage - it seems that their administration can be harmless and protective supplementation against numerous adverse effects of certain antineoplastic agents.
Keywords: cardiotoxicity